2014
DOI: 10.1002/chem.201402015
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Gold‐Catalyzed Synthesis of Dibenzocycloheptatrienes

Abstract: Dibenzocycloheptatrienes are obtained by a gold-catalyzed 7-exo-dig hydroarylation protocol in a highly efficient manner. The gold-catalyzed reaction usually gives the products in high yields and excellent selectivity. This procedure provides an easy and efficient access to dibenzocycloheptanoids, which are an interesting and unique class of natural products. This was underlined by the first total synthesis of reticuol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“… 367 Dibenzocycloheptatrienes were obtained by a related transformation through a 7- exo -dig hydroarylation. 368 …”
Section: Hydroarylation and Hydroheteroarylation Of Alkynesmentioning
confidence: 99%
“… 367 Dibenzocycloheptatrienes were obtained by a related transformation through a 7- exo -dig hydroarylation. 368 …”
Section: Hydroarylation and Hydroheteroarylation Of Alkynesmentioning
confidence: 99%
“…31 Although less commonly employed, these complexes proved to be far superior to phosphine and NHC-derived gold catalysts for the activation of the less reactive substrates and for enhancing the carbocationic character of the reactive inter-mediates in the addition of C-nucleophiles of 1,6-enynes 32 and in other processes. [33][34][35][36][37] Other related highly electrophilic complexes have also been developed. 38,39 A variety of chiral mono-and dinuclear phosphine, phosphite, and phosphoramidite gold complexes 26-34 have been developed for the enantioselective activation of alkynes and allenes (Fig.…”
Section: Gold(i) Precatalystsmentioning
confidence: 99%
“…After 24 hours, complete conversion was achieved giving a mixture of 2 a and 3 a in 99 % yield, determined by NMR spectroscopy, and a selectivity for 3 a of 8:1. In contrast to this result, the same reaction at room temperature without the additive gave 2 a as major product (Scheme ) 8…”
Section: Resultsmentioning
confidence: 78%
“…In our recent report on the synthesis of dibenzocycloheptatrienes,8 we found that for many catalyst systems and especially low‐catalyst loadings, a mixture of the primary 3 a and the rearranged product 2 a was obtained. Interestingly, 3 a was stable at ambient conditions and the obtained ratio 2 a / 3 a did not change by dissolution in CDCl 3 or during performance of column chromatography with silica gel.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation